SHADIQ DAWN OBSERVATION USING ALL SKY CAMERA IN DELI SERDANG, NORTH SUMATERA - Ritonga, Marataon; Rakhmadi, Arwin Juli; Qorib, Muhammad; Putraga, Hariyadi (ELFALAKY: Jurnal Ilmu Falak, 2024)
Technological advancements in optics and digital image recorders as means were breakthroughs in capturing and observing Shadiq Fajr's appearance which produce images according to visual as seen by the eye in the field. Digital camera usage such as the All-Sky Camera which is adjustable in taking dawn data according to a certain time, could show the sky conditions from dark to light, thus providing real evidence of the shadiq fajr appearance. Based on the research conducted, there are differences in Fajr prayer times based on the results of the observations by the All-Sky Camera with processed images using ImageJ and the Fajr prayer schedule issued by the Ministry of Religion of the Republic of Indonesia. Based on the image produced by ASC and processed using imagej, it shows that there is a change in the sky from dark to bright time which is characterized by significant graphic changes continuously. The study results obtained the average of the Sun depth at the Shadiq Fajr appearance is the altitude of 13.75 degrees below the horizon.